Gerard Genette Naratology on Gender Inequality from Alex L. Tobing’s Mekar Karena Memar - Fadhlan Ramadhan; Sulastri Sulastri; Rima Devi (Fakultas Sastra Universitas Ekasakti, 2023)
This research examines the gender inequality experienced by Gloria in Mekar Karena Memar's novel by Alex L. Tobing from Gerard Genette's narratology theory. The author is interested in studying gender inequality because, in this novel, the main character named Gloria is fighting against the gender inequality that she experiences. This makes this issue attractive to the author because women generally only received improper treatment without daring to do anything in those days. The author of the novel uses the pure narrative method, where the pure author acts like someone who is outside the novel and does not participate in the role of a character from the novel. In this study, the authors used a qualitative study method. The author collects data through literature study (documentation) and performs analysis using the Genette theory which consists of five parts: order, duration, frequency, mood, and voice. After analyzing, the writer found that the author had described the gender inequality experienced by a character named Gloria in the novel, as well as the actions Gloria had taken to overcome the gender inequality she experienced.